KONSEP JIWA DALAM TRADISI KEILMUAN ISLAM - EVI ZUHARA (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2018)
This article disccuses about soul concept in Islamic tradition of science. Soul is one of the main theme in mataphysical philosophy that become into a long debate between scientists both Muslim and Western. When it viewed from western tradition of science, mind stands in the high level that become the only benchmark to elaborate the meaning of soul. Due to it`s appraoach through mind, so western scientists just can understand souls problem from the side of empirical ratio by elaborating common principals and psychological symtomps. Usually in the hypothetical conclusions from ones` or reseachers` expereinces. That is what make vary of pshycological flows come up in the western tradition of science, it is cannot be apart from the point of view of flows founder in understanding souls only through mind dan impricial expereinces. Fundamental differences in Islam is in the soul’s placement in the ontology domain that has a thigt relationship with the God as the creator. The mind existence is as a logic theorem for the God existence. The soul’s explanation become wider because the revelation talks about it. In Al-quran and prophet traditions, soul at first as seminal concept, then developed it`s definition among Muslim scientists, philosopher, and sufis. Different perspective in understanding the meaning of soul among Muslims is the focus in this paper. Differences that come up only at the level of epistemology which in principle remains the same meaning, namely to know the position of humans as a creature that has a close relationship with God as Creator. Scientifically to know the nature of the soul, and by application as a servant to God.